The productivity of winter wheat in dependence on maintenance of elements of feed in soil - Барат, Ю. М. (Scientific Progress & Innovations, 2015)
The results of researches on the study of influencing of maintenance of elements of feed in soil on forming of the productivity of winter wheat are presented. It is set that the promoted maintenance of alkaline-hydrolysed nitrogen and exchange potassium in soil was instrumental in forming of the greater productivity of grain of crop of winter wheat. We did cards of feeds’ elements on which it is represented how this element is widespread on the field and in what amount. It enables to do the planned bringing of fertilizers on these coordinates. A norm will constantly change as well as we will plan it.